INSOMNIA AND CIRCADIAN RHYTHMS OF MELATONIN IN MENOPAUSAL WOMEN - N. V. Semenova (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
The aim of the review is to analyze literature data about sleep homeostasis and the role of the one of circadian system key elements – melatonin – in the regulation of the sleep-wake cycle in women in menopause. It was shown that the prevalence and structure of sleep disorders depends on the menopausal phase. It was revealed that the melatonin content in the body, determined in various biological media (blood, saliva, urine), depends on age, sex, race, and chronotype. It was shown that morning melatonin can be used as a biological marker for determining the chronotype. Most studies indicated a decrease in melatonin level with aging. Moreover, women have lower melatonin level than men. In case of insomnia, lower melatonin level was found, although the results of the studies are ambiguous. The shift in the peak of hormone secretion in the early morning hours was described in menopausal women. Also, the dependence of melatonin circadian rhythm on the menopausal phase was revealed, which determines different approaches to insomnia therapy. We revealed the association of melatonin secretion circadian rhythms with Clock 3111T/C gene polymorphism in Caucasian patients with insomnia, which allows considering 3111T allele as risky in the formation of melatonin circadian rhythm disturbances in these patients.